Patient's Adherence and Compliance and Quality of Life During/After VIT - Incorvaia, Cristoforo; Heffler, Enrico; Peveri, Silvia; Pucciarini, Francesco; Canonica, Giorgio Walter; Ridolo, Erminia (Frontiers in Allergy, 2022)
This review analyses the adherence to venom immunotherapy (VIT), in which, given its purpose of preventing potentially fatal anaphylactic reactions to insect stings, this aspect plays a critical role. In fact, protection from stings already takes place when the maintenance dose is reached, but VIT interruption before the recommended duration of 5 years exposes patients to new to sting reactions. The data on adherence to VIT are far less abundant than that for aeroallergen immunotherapy. One of the first studies reported a poor adherence in Austria, but the model used, consisting in the estimate of the percentage of patients with systemic reactions who accepted or rejected VIT, does not meet the criteria that define adherence to treatment. As for appropriate adherence studies, rates higher than 70% were reported in the United States and European countries. Studies from Italy found that a good adherence was observed also in patients receiving, after 4 years of VIT, 3 months extended maintenance dose, as well as in patients treated during Covid-19 pandemic, less than 10% of whom stopped VIT. Instead, only 35% of patientstreated for allergy to imported fire ant remained adherent after one year of treatment. However, also concerning honeybees and vespids, though adherence is satisfactory, it is possible to further improve it by increasing information and support for patients. Health related quality of life of life (HRQL) is an efficient measure to estimate the effectiveness and safety of medical treatment. Tools designed to make patients aware of its improvement through VIT, and in particular of the complete prevention of the risk of fatal reactions, have an important role in reinforcing adherence. However, aspects not yetevaluated, such as the possible relationship between the efficacy of VIT and HRQL or its particular features in patients with mastocytosis, deserve specific studies.